DAMPAK PENGEMBANGAN OBJEK WISATA DANAU LAET PADA PEREKONOMIAN MASYARAKAT DI DESA SUBAH - Siska, Siska; Sumartono, Bambang Genjik; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the impact caused by the development of Laet Lake tourism object on the economy of the community in Subah Village, Tayan Hilir District, Sanggau Regency. The research method used was a descriptive method with a qualitative approach and the form of research used was a survey. The data source in this study was the people who work around the tourism object that consist of 12 people as respondents to conduct the interviews. Data collection was obtained through interview guidelines, and then analyzed using data reduction, data presentation and verification/drawing conclusions, then checking the validity of the data using triangulation techniques. Researcher conducted research and interviews with people who worked around the tourism object twice. The results showed that the positive impact, it can be seen from the employment opportunities around the tourism object that were already very good and the income of the people around the tourism object was already very good.Key words: Community?s Economy, Impact of Tourism Object Development